(untitled) (Revista Electrónica REDINE, 2025)
The arrival of the COVID 19 pandemic decreed by the World Health Organization in 2020, drastically affected all the established orders in society worldwide, with economic, social, historical and, of course, educational changes. The context exposes the complexity of the process of sustainable human development, because it requires a high level of awareness and appreciation by human beings of their relationship with the planet earth. Hence, the purpose of the reflective discourse of the essay is to interpret the educational process in Venezuela from the arrival of the pandemic to the present, in the sustainable aspect and within the framework of a curriculum under the slogan “Together for the Education of the Future”. To this end, we reflect on the curricular strategic lines for the 2022-2023 school year. Environmental education materialized in the implementation of the “All Hands to Plant” Program; which implies a view to changes in the modes of production to ensure the protection and preservation of the environment; with the participation of families and all educational actors in a conscious and permanent way, in the formation of the student in the framework of sustainable human development. In addition, it is interesting how the issue of family participation in the teaching and learning processes that are closely related to sustainable human development occurs in the Venezuelan educational praxis.